Fundamental Groups and Covering Spaces. - Lima, Elon Lages (CRC Press, 2003)
"This introductory textbook describes fundamental groups and their topological soul mates, the covering spaces. The author provides several illustrative examples that touch upon different areas of mathematics, but in keeping with the books introductory aim, they are all quite elementary. Basic concepts are clearly defined, proofs are complete, and no results from the exercises are assumed in the text."--Provided by publisher